Relationship between parenting style and academic achievement among Iranian adolescents in Sirjan - Dehyadegary, Elham; Yaacob, Siti Nor; Juhari, Rumaya; Abu Talib, Mansor (Canadian Center of Science and Education, 2012)
The purpose of the present study was to determine the relationship between parenting styles and academic achievement among adolescents in Iran. The respondents were 382 high school adolescents (251 female and 131 male) in the age range of 15 to 18 years old from selected high schools in Iran. The instrument used to measure parenting style was the parenting style scale by Baumrind (1991). The result of the study indicated that authoritative parenting style has positive significant correlation with academic achievement, while permissive parenting style has negative correlation with academic achievement. The result of the study also showed that there is no significant relationship between authoritarian parenting style and academic achievement. The results of the present study implied that academic achievement among adolescents can be enhanced through positive parenting style. Thus, it is recommended that parents be equipped with knowledge and skills appropriate to the needs and development of their adolescents children.